Caracterización de los Parámetros reproductivos de Cuyes en la segunda Progenie de cruce Genético de Tipo Absorbente. - Tayupanda Caisaguano, Tania Paola (2017)
The characterization of the reproductive parameters in guinea pigs was carried out under the identification, tabulation, handling and standardization of guinea-pig registries according to the phenotypic characteristics. Under the following objectives: To verify the characteristics of selected guinea pigs in the first progeny using genetic selection parameters in the reproductive stage to establish improvement. To evaluate the improved animals in the first progeny by the relation to their characteristics of the genetic value in the reproductive stage to establish genetic improvement and to relate the most outstanding genetic characteristics of the guinea pigs in the reproductive stage of the first and second progeny by comparative analysis Performed. Obtaining the following results based on the categories identified, as the best category 4 (whites) with 4 offspring per delivery. In category 4 (whites) we identified an average of 2 of the offspring born, in category 1 colored with whirlpool a mean 1.71y of category 2 colored without whirlpool have an average of 1.71, the category 3 bays has an average of 1.86 and in category 5 painted with swirl has an average of 1.90, in category 6 painted with swirl has an average of 1.75. Identifying category 4 (whites) with a calving of 4 offspring with an average of 2 that are identified as animals with good reproductive characteristics. Concluding that the best category of guinea pigs was identified by the color of fur and meeting the reproductive parameters was identified the category 4 targets by means of the selection parameters. For the selection of guinea pigs as genetically improved animals, the Pearson correlation was used, which facilitated the identification of the guinea pigs that fulfilled the reproductive parameters, being identified by their high genetic value and their conception of 4 pups per calving. In the correlation of progeny 1 and progeny 2 it was identified as null significance since the value of (p = 0).